Bovine Coronavirus Immune Milk Against COVID-19 - Arenas, Antonio; Borge, Carmen; Carbonero, Alfonso; Garcia-Bocanegra, Ignacio; Cano-Terriza, David; Caballero, Javier; Arenas-Montes, Antonio (Frontiers in Immunology, 2021)
After a year of evolution of the SARS-CoV-2 epidemic, there is still no specific effective treatment for the disease. Although the majority of infected people experience mild disease, some patients develop a serious disease, especially when other pathologies concur. For this reason, it would be very convenient to find pharmacological and immunological mechanisms that help control SARS-CoV-2 infection. Since the COVID-19 and BCoV viruses are very close phylogenetically, different studies demonstrate the existence of cross-immunity as they retain shared epitopes in their structure. As a possible control measure against COVID-19, we propose the use of cow's milk immune to BCoV. Thus, the antigenic recognition of some highly conserved structures of viral proteins, particularly M and S2, by anti-BCoV antibodies present in milk would cause a total or partial inactivation of SARS-COV-2 (acting as a particular vaccine) and be addressed more easily by GALT's highly specialized antigen-presenting cells, thus helping the specific immune response.